2022
DOI: 10.1177/23333936221097113
|View full text |Cite
|
Sign up to set email alerts
|

Alberta Family Integrated Care™ and Standard Care: A Qualitative Study of Mothers’ Experiences of their Journeying to Home from the Neonatal Intensive Care Unit

Abstract: Globally, one in ten infants is born preterm. Most preterm infants require care in a level II Neonatal Intensive Care Unit (NICU), which are highly technological critical care environments that can be overwhelming for parents. Alberta Family Integrated Care (AB-FICare™) is an approach to care that provides strategies to integrate parents into their infant’s care team. This sub-study is the first to compare mothers’ experiences in the context of AB-FICare™ and standard care. Semi-structured interviews with moth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Parents have described the discharge process as going through phases, and have argued that being suddenly faced with going home or being rushed through information provision could add to stress. 15,18,22 Our study showed that even though initial information was given soon after admission, detailed and extensive planning and education were often postponed until the last one to 2 weeks before discharge. As early parental involvement in infant care and rooming-in are standard in many Nordic NICUs, a continuous training process in cooperation with parents with a clear focus on going home could be implemented.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Parents have described the discharge process as going through phases, and have argued that being suddenly faced with going home or being rushed through information provision could add to stress. 15,18,22 Our study showed that even though initial information was given soon after admission, detailed and extensive planning and education were often postponed until the last one to 2 weeks before discharge. As early parental involvement in infant care and rooming-in are standard in many Nordic NICUs, a continuous training process in cooperation with parents with a clear focus on going home could be implemented.…”
Section: Discussionmentioning
confidence: 82%
“…1,5,8 Earlier discharge to home-based care could be beneficial but requires an understanding of the criteria and preparations important for safe discharge, and of how to assess infant and parent readiness. 3,[9][10][11][12][13][14][15] Cardiorespiratory stability 14,16 is considered a prerequisite for discharge and determines when continuous monitoring of heart rate or oxygen saturation can be discontinued. 12 Clinical evaluation of cardiorespiratory stability is usually done by bedside observation and documentation of apnoeas and bradycardias, sometimes complemented with more formal pre-discharge tests.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In countries across the world, family-integrated care (FICare) has become a standard of care, in which parents are integrated into the care team as equal members and as partners who deliver the majority of infant care in the NICU. 4-7 FICare results in benefits for both parents and infants, including demonstrated improvements in infant weight gain and exclusive breastfeeding rates, NICU length of stay, parent confidence and involvement in infant care, parent–infant bonding, and lower symptoms of parent stress, anxiety, and depression 1,4,8-13. Formal FICare programs do provide structured training to parents through the Parent Education pillar of FICare, in which parents learn how to care for their infant through required parent presence at the bedside (eg, 6-8 hours a day for 5 days a week), frequent small group education sessions, and participation in bedside rounds.…”
mentioning
confidence: 99%
“…[4][5][6][7] FICare results in benefits for both parents and infants, including demonstrated improvements in infant weight gain and exclusive breastfeeding rates, NICU length of stay, parent confidence and involvement in infant care, parent-infant bonding, and lower symptoms of parent stress, anxiety, and depression. 1,4,[8][9][10][11][12][13] Formal FICare programs do provide structured training to parents through the Parent Education pillar of FICare, in which parents learn how to care for their infant through required parent presence at the bedside (eg, 6-8 hours a day for 5 days a week), frequent small group education sessions, and participation in bedside rounds. Through prolonged parent presence and engagement with the care team, parents not only learn how to complete a wide range of infant care tasks but also learn how to comanage complex care in the NICU as members of the care team.…”
mentioning
confidence: 99%